POTENSI DAMPAK DISPERSI POLUTAN KARBON MONOKSIDA TERHADAP KESEHATAN PENDUDUK DI SEKITAR PINTU TOL BARANANGSIANG BOGOR - Paramitadevy, Yudith Vega; Yuwono, Arief Sabdo; Widyarti, Meiske (Bumi Lestari; Vol 17 No 1 (2017), 2017)
Over the past decade, emission from carbon monoxide (CO) has risen due to the increase of vehicles per year. Bogor as a weekend tourist town has a heavy burden in terms of the volume of motor vehicles. Object in this study is Baranangsiang Bogor toll gateway which often occurs queue of motor vehicles and allegedly produces many pollutants CO.This study was conducted to simulate the CO concentration by the method of Finite Length Line Source (FLLS) around Baranangsiang Bogor toll gateway and recapitulate types of diseases associated with CO impacts on communities around the toll is in line with the pattern of increase in the volume of vehicles at 6 % per years. Based on the results of measurements and simulations were conducted on four sampling points within 20 m and 190 m from the sources of pollution on 29 August to 1 September 2013, the concentration of CO is still within the range of quality standards in accordance with Regulation No. 41 of 1999 which is 634-9189 ìg/Nm . Dispersion of pollutants CO dominantly heading eastwards with the wind speed measurements 1.5-5.2 m/ s and atmospheric stability class B. Kampung Sawah RT 02 RW 07 is exposed to higher CO. Recapitulation of medical records showed that CO intoxication suspected cases of the disease are more common in Kampung Sawah housing than Perumahan Pegawai IPB  Baranangsiang 4.